Bladder preservation in older adults with muscle-invasive bladder cancer: A retrospective study with concurrent chemotherapy and twice-daily hypofractionated radiotherapy schedule. Issue 7 (September 2022) - Alati, Aurélia; Fabiano, Emmanuelle; Geiss, Romain; Mareau, Alexis; Charles-Nelson, Anais; Bibault, Jean-Emmanuel; Giraud, Philippe; Kreps, Sarah; Méjean, Arnaud; Housset, Martin; Durdux, Catherine
Abstract: Introduction: Bladder cancer occurs mainly in older adults and surgery is not always possible when there are geriatric conditions and comorbidities. Trimodal treatment (TMT) combining trans-urethral resection of bladder tumour (TURBT) followed by concurrent chemoradiation (CRT) would be a curative alternative in such patients. Materials and Methods: All consecutive patients 75 years of age and older with non-metastatic muscle-invasive bladder cancer (MIBC) treated with TMT by Georges Pompidou European Hospital team were retrospectively analysed. Induction CRT combined hypofractionated twice-daily radiotherapy targeting bladder and pelvis to a total dose of 24 Gy (Gy) with concurrent platinum salt and 5-fluorouracil. Consolidation CRT to a total dose of 44 Gy was proposed to patients with biopsy-proven complete response after induction phase and those with persistent tumour underwent salvage cystectomy. We assessed using Kaplan-Meier method overall survival (OS), cancer specific survival (CSS), invasive recurrence-free survival (IRFS), metastasis-free survival (MFS), survival with bladder preserved (SBP), and toxicities. With a Cox model for OS and the Fine Gray method of competing risk for secondary endpoints, we analysed in univariate (u) and multivariate (m) analysis the impact of tumour characteristics and patient profiles: gender, age, age-adjusted Charlson comorbidity index, polypharmacy, and malnutrition. Results: From 1988 to 2017, 85 patients were included. After induction, complete response rate was 83.5%. With a median follow-up of 63 months, 5 year-OS, CSS, IRFS, MFS and SBP were 61.0%, 77.6%, 71%, 82.9%, and 70.2% respectively. A persistent tumour after induction impacted SBP (SHRm 3.61; p = 0.004), CSS (SHRm 3.27; p = 0.023), and MFS (SHRm 3.68; p = 0.018). Late grade 3 urinary and gastrointestinal toxicities were 3.5% and 1.2%. Discussion: We report here the largest series of bladder preservation over 75 years in a curative intent. Outcomes and tolerance in selected older adults compared favourably with surgical series and with CRT studies using classical fractionation.